PENERAPAN CSR (CORPORATE SOCIAL RESPONSIBILITY) MELALUI SINERGITAS ANTARA SEKOLAH MENENGAH KEJURUAN (SMK) DENGAN PENGRAJIN KERIS DI KABUPATEN SUMENEP - Bagus Ananda Kurniawan (UII, 2015)
The problem of unemployment in Indonesia each year has increased. Open unemployment is dominated by youth unemployment. East Java Province with the number of unemployed become the 3rd largest after West Java and Jakarta. Sumenep menjedi one contributor to the number of unemployed in the island of Madura. Based on data obtained As of mid-2014, the unemployment rate is still high in Sumenep. Several companies and government agencies have not been able to adequately absorb labor. Evidently, the number of unemployed up to now reaches 23 618 inhabitants. Data Manpower and Transmigration (Manpower), of 40 762 inhabitants job seekers (pencaker), which absorbed until July 2014 just as much as 17 144 inhabitants. Thus, the remaining 57.94 per cent pencaker are still unemployed. This is contrary to the initial setting SMK prepared to be ready to work according to the department and the competence of existing jobs. Some things yan lead to vocational school graduates do not get jobs, among others, the lack of cooperation in terms of publications between the Vocational High School (SMK) and the company, the lack of synergy between government enterprises, vocational, and Office as well as SMEs craftsmen Sumenep involved in prevention increased the number of unemployed, as well as the incompatibility of competency of vocational graduates with the power needed by the company. Implementation of CSR (Corporate Social Responsibility) through Synergy Between Vocational High School (SMK) With Custom Kris is expected to be able to reduce the number of unemployed, especially young in vocational schools (SMK)There are five steps in the implementation of the application of this CSR, the steps initiated by the Establishment of the program by the government of Sumenep for vocational students there are two in the form of a business plan competition took groups of SMEs of making Keris In Sumenep regency. Next is the stage of socialization into each vocational program launched on pemerintah.Kabupaten Sumenep in practice later after passing the stage of selection of proposals for SME groups that submitted proposals Keris-making and data collection number of students who will be directed and focused to help groups of SMEs of making Keris in Sumenep. mentoring by a group of SMEs manufacture Keris in Sumenep direct and control of the government done to the smooth running of this program. so that later can produce output in the form of education results of entrepreneurship development program as a form of early or pioneer group of SMEs Making Keris in Sumenep. Keywords: CSR, SMK, synergy, Craftsman Keris in Sumenep